2005
DOI: 10.1051/0004-6361:20041353
|View full text |Cite
|
Sign up to set email alerts
|

Astrometric and spectroscopic confirmation of a brown dwarf companion to GSC 08047-00232

Abstract: Abstract. We report VLT/NACO imaging observations of the stars GSC 08047-00232 and HIP 6856, probable members of the large Tucana-Horologium association. During our previous ADONIS/SHARPII deep imaging survey, a substellar candidate companion was discovered around each star. Based on VLT/NACO astrometric measurements, we find that GSC 08047-00232 and the faint candidate companion near to it share the same proper motion with a significance of 3.1 σ. On the contrary, the candidate companion to HIP 6856 is probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 33 publications
3
27
1
Order By: Relevance
“…Our strategy has been sucessful with the confirmation of a brown dwarf companion to GSC 08047-00232 (Chauvin et al 2003(Chauvin et al , 2005a and discoveries of a planetary mass companion to the young brown dwarf 2MASSW J1207334-393254 (hereafter 2M1207; Chauvin et al 2004;2005c) and a companion at the planet/brown dwarf boundary to the young star AB Pic (Chauvin et al 2005b).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our strategy has been sucessful with the confirmation of a brown dwarf companion to GSC 08047-00232 (Chauvin et al 2003(Chauvin et al , 2005a and discoveries of a planetary mass companion to the young brown dwarf 2MASSW J1207334-393254 (hereafter 2M1207; Chauvin et al 2004;2005c) and a companion at the planet/brown dwarf boundary to the young star AB Pic (Chauvin et al 2005b).…”
Section: Resultsmentioning
confidence: 99%
“…Many such stars reside in several coeval moving groups (e.g., TWA, β Pictoris, Tucana-Horologium, η Cha, AB Dor, Columba and Carinae), sharing common kinematics, photometric and spectroscopic properties (see Zuckerman & Song 2004, hereafter ZS04;Torres et al 2008, T08). A few young brown dwarf companions have been detected from space, HR 7329 B and TWA5 B (Lowrance et al 2000(Lowrance et al , 1999, and from the ground, GSC 08047-00232 B (Chauvin et al 2005a). Companions down to the planetary mass regime were discovered around the star AB Pic (Chauvin et al 2005c) and the young brown dwarf 2M1207 (Chauvin et al 2004(Chauvin et al , 2005b.…”
Section: Introductionmentioning
confidence: 99%
“…However, its near-IR gravity status is uncertain, as Allers & Liu (2013a) type this object as L6 int-g but Gagné et al (2015a) typed it as L6p with no clear sign of low gravity. TVLM831-154910 has a parallax from Tinney et al (1995) and has recently been typed as M7:β vl-g and identified 5 Four well-known young ultracool companions are not included in our compilation as their primary stars lack parallaxes: GSC 08047−00232 B (M9.5±1, Tuc-Hor member; Chauvin et al 2003;Neuhäuser & Guenther 2004;Chauvin et al 2005a), 1RXS J235133.3+312720 (L0 +2 −1 , probable AB Dor member; Bowler et al 2012), 2MASS J01225093−2439505 B (L3.7±1.0, probable AB Dor member; Bowler et al 2013;Hinkley et al 2015), and GU Psc b (T3.5±1, probable AB Dor member; Naud et al 2014).…”
Section: Objects Not Included In Our Analysismentioning
confidence: 99%
“…It is sensitive to intrinsically bright objects (low-mass stars, brown dwarfs, and young giant planets), and it brings essential insight to the possible origins of these objects . Direct near-infrared imaging allowed observers to detect several kinds of substellar companions, such as brown dwarfs (e.g., Nakajima et al 1995;Lowrance et al 1999Lowrance et al , 2000Chauvin et al 2005a), objects at the transition between brown dwarfs and planets (e.g., Chauvin et al 2005b), or planetary-mass objects such as 2M1207b in orbit around a brown dwarf (Chauvin et al 2004(Chauvin et al , 2005c, all of which are probably not formed through core-accretion like planets detected by velocimetry, but rather as multiple stars via a cloud fragmentation process or as brown dwarfs through disc fragmentation (see, e.g., Lodato et al 2005). These detections nevertheless show that star-forming mechanisms can be efficient down to planetary masses.…”
Section: Introductionmentioning
confidence: 99%